Implementation Of Integrated Quality (Mmt) In Improving The Quality Of Open High School Graduates - Wardhana, Nanang; Wasliman, Iim; Warta, Waska; Cepi Barlian, Ujang (International Journal of Educational Research & Social Sciences, 2022)
The number of limitations/obstacles experienced by some graduates of SMP/MTs who cannot continue their education to a higher level, namely High School/SMK/MA due to several limitations, among others: due to financial factors of parents, children as the backbone of the family, geographical conditions experienced by some participants students to regularly come every day to a regular high school, as well as the difficulty of public transportation as access to school.The purpose of this research is to find out how the implementation of Integrated Quality Management (MMT) in improving the quality of graduates of SMA Open actually through the management theory approach "Daming Cycle" from W. Edward Daming. In particular, this study describes and analyzes (1) plan, (2) Do, (3) Check and (4) action about open high school using the quality theory of Sallis Edward. This study uses a descriptive method with a qualitative approach. Collecting data by conducting observations, interviews, and documentation studies. From the results of the study, it shows that Integrated Quality Management (MMT) in improving the quality of graduates of Open High School in National High School and March 11 High School has been carried out by adjusting the existing concept rules although in its implementation there are still obstacles, especially in terms of commitment of parents and students, limited budget from the government and difficulties in getting visiting teachers who are committed to providing flexible learning.